Conductive dendritic crystal composite gel as well as preparation method and application thereof

By depositing metal tin dendrites in situ inside the hydrogel to construct a conductive dendrites composite gel, the problems of insufficient conductivity and mechanical properties of existing conductive hydrogels are solved, and efficient conductivity and good tensile toughness are achieved, which are suitable for wearable sensors.

CN119591906AActive Publication Date: 2025-03-11ZHEJIANG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411703870.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

When existing conductive hydrogels improve conductivity, the commonly used electronic conductive fillers are unevenly dispersed, resulting in poor interaction between the polymer matrix and the filler, and the rigidity of the filler will deteriorate the tensile properties of the gel, resulting in low efficiency problems.

Method used

Using hydrogel as the matrix, metal tin dendrites are deposited in situ inside it to build a conductive pathway, and the hydrophilicity of the hydrogel skeleton attracts stannous ions, promotes the deposition of tin dendrites, and forms a conductive dendrites composite gel.

Benefits of technology

By building a 3D conductive dendrite network, the conductivity and mechanical properties of the gel are significantly improved, the conductivity and tensile toughness of the gel are enhanced, and it is suitable for wearable flexible strain sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005154057780000011
    Figure HDA0005154057780000011
  • Figure HDA0005154057780000012
    Figure HDA0005154057780000012
  • Figure HDA0005154057780000013
    Figure HDA0005154057780000013
Patent Text Reader

Abstract

The invention discloses conductive dendritic crystal composite gel as well as a preparation method and application thereof. According to the invention, hydrogel is used as a matrix, stannous ions are attracted by utilizing the hydrophilicity of a hydrogel skeleton, and metal dendrites are further deposited in situ in the gel, so that an efficient conductive path is constructed; the mechanical property and the conductivity of the conductive dendritic crystal composite gel are synchronously improved; besides, a sensor prepared based on the conductive dendritic crystal composite gel has high sensitivity and a wide detection range, can effectively monitor and identify limb changes, and shows wide application potential in the field of wearable equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a conductive dendrite composite gel and a preparation method and application thereof. Background Art

[0002] With the rise of flexible smart devices and their wide application, the development of flexible wearable devices has received increasing attention. As a three-dimensional soft material composed of polymers and water, hydrogel is regarded as a reliable matrix material for flexible devices because of its properties similar to human tissues and good biocompatibility. At present, conductive hydrogels are mainly divided into two types: ion conductive and electronic conductive. Common strategies to improve the conductivity of gels include using conductive polymers or adding conductive fillers. However, these electronic conductive fillers usually need to be dispersed in the desired gel precursor and undergo additional ultrasonic treatment before polymerization and cross-linking. Therefore, the above method has the following shortcomings:

[0003] 1) Hydrophobic fillers tend to aggregate in aqueous precursors, resulting in uneven filler distribution and weakened polymer matrix-filler interactions; 2) The system becomes more complicated by adding additives such as cellulose nanofibers, polydopamine, and surfactants to promote filler dispersion; 3) Some conductive fillers may interfere with the polymerization process, and their rigid properties will also deteriorate the tensile properties of the hydrogel. Although ion conductive fillers generally do not have the above problems, the currently developed conductive hydrogels often face the problem of low efficiency.

[0004] Therefore, how to construct a simple and efficient pathway inside the gel without compromising its mechanical properties remains an important issue that needs to be solved urgently. Summary of the invention

[0005] To solve the above technical problems, the present invention proposes a conductive dendrite composite gel and its preparation method and application. The present invention uses hydrogel as a matrix and in-situ deposits metal tin dendrites inside the gel to construct a conductive path, thereby preparing a conductive dendrite composite gel.

[0006] In this design system, the hydrophilicity of the hydrogel skeleton is used to attract stannous ions, thereby promoting the in-situ deposition of tin dendrites. At the same time, the three-dimensional metal dendrite network can effectively provide a conductive path to improve the conductivity of the gel. In addition, the coupling between the rigid metal dendrites and the flexible gel achieves a significant improvement in the mechanical properties of the dendrite composite gel.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a conductive dendrite composite gel comprises the following steps:

[0009] 1) dispersing a vinyl monomer, a photoinitiator and a crosslinking agent in water by ultrasonication to obtain a polymer prepolymer solution, and then initiating a polymerization reaction under ultraviolet light (365 nm) to form a hydrogel;

[0010] The vinyl monomer is selected from: 2-acrylamido-2-methylpropanesulfonic acid (AMPS), acrylamide (AM), [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide (SBAA), 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (SBMA), dimethyl-(4-vinylphenyl)ammonium propane sulfonate (DVBAPS) or 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate (VBIPS) and the like, preferably 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium)propane-1-sulfonate (VBIPS);

[0011] The photoinitiator is selected from: 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (2959), 2-hydroxy-2-methyl-1-phenylpropanone (1173), 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone (907), 1-hydroxycyclohexylbenzophenone (184) or 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), preferably 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (2959);

[0012] The cross-linking agent is selected from: molecules containing more than two double bonds such as N,N-dimethylacrylamide (DMAA) and N,N-methylenebisacrylamide (MBA);

[0013] Preferably, in the polymer prepolymer solution, the content of the vinyl monomer is 1 to 8 mmol / mL, the content of the photoinitiator is 0.1 to 1 wt%, and the content of the crosslinking agent is 0.05 to 2 wt%;

[0014] The polymerization temperature is room temperature and the time is 0.5 to 12 hours;

[0015] 2) soaking the hydrogel obtained in step 1) in a stannous chloride solution to obtain a hydrogel rich in stannous ions;

[0016] Preferably, the concentration of the stannous chloride solution is 0.05 to 6 mol / L, and the soaking time is 2 to 48 hours;

[0017] In the preparation of stannous chloride solution, in order to prevent the hydrolysis of stannous ions, anhydrous stannous chloride is first dissolved in hydrochloric acid (1-10 mol / L), and then diluted with water to the required concentration;

[0018] 3) Externally connecting electrodes to both ends of the hydrogel rich in stannous ions obtained in step 2) and applying voltage to induce in-situ deposition of dendrites, followed by soaking and dialysis with deionized water to remove free Sn. 2+ ions, and a conductive dendrite composite gel is obtained;

[0019] The external electrode is a metal tin electrode, the applied voltage range is 1 to 10 V, and the power-on time is 1 to 10 minutes;

[0020] The dialysis time of deionized water soaking is 12 to 60 hours, and the deionized water is replaced several times during the soaking process.

[0021] The invention relates to a conductive dendrite composite gel prepared by the preparation method.

[0022] The conductive dendrite composite gel of the present invention can be used as a wearable flexible strain sensor. The specific method is, for example: connecting the two ends of the conductive dendrite composite gel to an electrochemical workstation through copper tape and a wire, and at the same time, using 3M VHB tape to package both sides of the gel to achieve the construction of a flexible strain sensor.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The conductive dendrite composite gel provided by the present invention exhibits good mechanical toughness (2.3MJ / m 3 ), and has good crack passivation ability and high fracture toughness (720kJ / m 2 ), which is beneficial to the daily long-term use of the conductive gel.

[0025] 2. The 3D conductive dendrite network constructs an excellent conductive pathway inside the gel, making the conductive composite gel exhibit excellent conductive properties (12.5S / m), which can be used as a sensor to detect and identify human body movements. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : Schematic diagram of the preparation of the conductive dendrite composite gel of the present invention.

[0027] Figure 2 : Schematic diagram of the structure of the flexible strain sensor prepared by encapsulation of the present invention.

[0028] Figure 3 : Swelling kinetics curves and appearance photos of gels with different molecular structures in Examples 1 to 4 in stannous chloride solution.

[0029] Figure 4 : Swelling kinetics curves of the gels in Examples 1, 5, 6 and 7 in stannous chloride solutions of different concentrations.

[0030] Figure 5 : Dendrite growth of the gels immersed in stannous chloride solutions of different concentrations under different voltages in Examples 1, 5, 6 and 7.

[0031] Figure 6 : Gel after induction of dendrite in-situ deposition under different concentrations of stannous chloride solution in Examples 1, 5, 6 and 7 and removal of excess Sn by soaking in water 2+ Photo of the appearance of the ionic post-dendritic composite gel.

[0032] Figure 7 : The tensile curves, Young's modulus and tensile toughness of the dendrite composite gel and pure gel prepared in Example 1 and Comparative Example 1.

[0033] Figure 8 : Fracture toughness of the dendrite composite gel and pure gel prepared in Example 1 and Comparative Example 1. The illustration shows the change of the dendrite composite gel containing notches under different strains.

[0034] Fig. 9 : Comparison of the electrical conductivity of the dendrite composite gel prepared in Example 1 and Comparative Example 1 with that of the pure gel.

[0035] Fig.10 : Resistance changes of the sensor prepared based on dendrite composite gel under different strains in Example 1.

[0036] Fig.11 : Resistance changes caused by different gestures when the sensor prepared based on dendrite composite gel in Example 1 is worn on a finger. DETAILED DESCRIPTION

[0037] The present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the following description is only the most preferred embodiment of the present invention and should not be regarded as limiting the scope of protection of the present invention.

[0038] Example 1

[0039] First, 1.22g (4mmol) VBIPS monomer, 0.01g photoinitiator 2959, and 0.003g crosslinker MBA were dispersed in 0.97mL deionized water, and then ultrasonically treated for 10min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365nm ultraviolet light for 4h to polymerize to obtain pVB hydrogel. The hydrogel was then immersed in a 2mol / L stannous chloride solution for 24h to fully absorb Sn. 2+ Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0040] The above-mentioned conductive dendrite composite gel can be used as a wearable flexible strain sensor, and the steps are as follows: connect the two ends of the prepared dendrite composite gel to the electrochemical workstation through copper tape and wires, and at the same time, use 3M VHB tape to encapsulate both sides of the gel to realize the construction of a flexible strain sensor.

[0041] Example 2

[0042] First, 1.11 g (4 mmol) SBMA monomer, 0.01 g photoinitiator 2959 and 0.003 g crosslinker MBA were dispersed in 1.08 ml deionized water, and then ultrasonically treated for 10 min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365 nm ultraviolet light for 4 h to polymerize to obtain pSB hydrogel. The hydrogel was then immersed in a 2 mol / L stannous chloride solution for 24 h to fully absorb Sn. 2+ Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0043] Example 3

[0044] First, 0.28 g (4 mmol) AM monomer, 0.01 g photoinitiator 2959 and 0.003 g crosslinker MBA were dispersed in 1.91 ml deionized water, and then ultrasonically treated for 10 min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365 nm ultraviolet light for 4 h to polymerize to obtain pAM hydrogel. The hydrogel was then immersed in a 2 mol / L stannous chloride solution for 24 h to fully absorb Sn. 2+ Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0045] Example 4

[0046] First, 0.83 g (4 mmol) of AMPS monomer, 0.01 g of photoinitiator 2959 and 0.003 g of crosslinker MBA were dispersed in 1.23 ml of deionized water, and then ultrasonically treated for 10 min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365 nm ultraviolet light for 4 h to polymerize to obtain pAMPS hydrogel. The hydrogel was then immersed in a 2 mol / L stannous chloride solution for 24 h to fully absorb Sn. 2+Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0047] Example 5

[0048] First, 1.22g (4mmol) VBIPS monomer, 0.01g photoinitiator 2959, and 0.003g crosslinker MBA were dispersed in 0.97ml deionized water, and then ultrasonically treated for 10min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365nm ultraviolet light for 4h to polymerize to obtain pVB hydrogel. The hydrogel was then immersed in a 0.5mol / L stannous chloride solution for 24h to fully absorb Sn. 2+ Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0049] Example 6

[0050] First, 1.22g (4mmol) VBIPS monomer, 0.01g photoinitiator 2959, and 0.003g crosslinker MBA were dispersed in 0.97ml deionized water, and then ultrasonically treated for 10min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365nm ultraviolet light for 4h to polymerize to obtain pVB hydrogel. The hydrogel was then immersed in 1mol / L stannous chloride solution for 24h to fully absorb Sn. 2+ Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0051] Example 7

[0052] First, 1.22g (4mmol) VBIPS monomer, 0.01g photoinitiator 2959, and 0.003g crosslinker MBA were dispersed in 0.97ml deionized water, and then ultrasonically treated for 10min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365nm ultraviolet light for 4h to polymerize to obtain a hydrogel. The hydrogel was then immersed in a 4mol / L stannous chloride solution for 24h to fully absorb Sn. 2+Furthermore, tin electrodes were connected to both ends of the equilibrated gel and the voltage was controlled to be 10V to induce in-situ deposition of dendrites in the gel. Finally, after energizing for 3 minutes, the gel was immersed in a large amount of deionized water for dialysis to obtain a conductive dendrite composite gel.

[0053] Comparative Example 1

[0054] First, 1.22g (4mmol) VBIPS monomer, 0.01g photoinitiator 2959, and 0.003g crosslinker MBAA were dispersed in 0.97ml deionized water, and then ultrasonically treated for 10min to obtain a polymer precursor solution. Then, the polymer precursor solution was injected into the mold using a syringe and placed under 365nm ultraviolet light for 4h to initiate polymerization to obtain pVB hydrogel. Finally, the prepared hydrogel was immersed in a large amount of deionized water to remove unreacted small molecules in the gel.

[0055] The gel samples prepared in Examples 1 to 7 and Comparative Example 1 were tested, and the test results are as follows: Figures 1 to 11 As shown below, combined Figures 1 to 11 To explain:

[0056] Figure 1 It is a schematic diagram of the preparation of the conductive dendrite composite gel based on the present invention; the hydrogel is immersed in a stannous chloride solution and then an external electrode is used to induce in-situ deposition of metal tin ions in the gel network. Finally, the gel covered with dendrites is immersed in deionized water and dialyzed to remove free ions to obtain a conductive dendrite composite gel.

[0057] Figure 2 Schematic diagram of the structure of the strain sensor prepared for encapsulating conductive dendrite composite gel. Specifically, VHB double-sided tape is used to encapsulate the gel on both sides to achieve better fit between the gel and the human body and more lasting water retention.

[0058] Figure 3 The swelling kinetic curves and gel photos of hydrogels with different molecular structures in Examples 1 to 4 in stannous chloride solution show that the pVB gel exhibits more obvious swelling characteristics in the stannous chloride solution due to the strong anti-polyelectrolyte effect, the pAMPS gel shrinks due to its polyelectrolyte effect, and the pAM gel has no obvious volume change in the stannous chloride solution due to its non-ionic properties.

[0059] Figure 4 The swelling kinetic curves of the pVB hydrogels in Examples 1, 5, 6 and 7 in stannous chloride solutions of different concentrations show that the swelling rate of the gel increases synchronously with the increase in solution concentration, which is consistent with the law of the gel anti-polyelectrolyte effect, and the swelling rate reaches a maximum of 900% in a solution with a concentration of 4 M.

[0060] Figure 5The dendrite growth of pVB hydrogels immersed in stannous chloride solutions of different concentrations at different voltages in Examples 1, 5, 6 and 7 is shown. The gel immersed in high-concentration stannous chloride solution has the fastest dendrite growth rate in the early stage due to the rapid nucleation of dendrites induced by more salt ions inside the gel.

[0061] Figure 6 These are appearance photographs of the gels after being immersed in stannous chloride solutions of different concentrations and inducing in-situ deposition of dendrites in Examples 1, 5, 6 and 7, and the dendrite composite gels after being finally soaked in water to remove free ions.

[0062] Figure 7 The tensile curves, statistical Young's modulus and tensile toughness of the dendrite composite gel and pure gel prepared in Example 1 and Comparative Example 1 are shown in Figure 1. The modulus of the dendrite composite gel based on the present invention is 0.6 MPa, and the tensile toughness is as high as 2.3 MJ / m 3 , compared with the pure gel without dendrites, the tensile toughness is significantly improved.

[0063] Figure 8 The fracture toughness of the dendrite composite gel and pure gel prepared in Example 1 and Comparative Example 1 is shown in the figure. The inset is a photograph of the dendrite composite gel containing a notch under different strains. The fracture toughness of the dendrite composite gel based on the present invention is 1334 J / m 2 , compared with the dendrite-free gel prepared in Comparative Example 1, the fracture toughness is significantly improved, and the inset shows that the dendrite composite gel has crack passivation ability.

[0064] Fig. 9 The conductivity of the dendrite composite gel and pure gel prepared in Example 1 and Comparative Example 1 is compared. The dendrite composite gel of the present invention has excellent conductive properties due to the introduction of a conductive dendrite network, and the conductivity is as high as 12.5 S / m.

[0065] Fig.10 The resistance change of the sensor prepared based on the dendrite composite gel under different strains in Example 1 shows obvious resistance change under small strain and large strain, and the signal has good stability after five cycles, which proves the high sensitivity and wide range detection capability of the sensor.

[0066] Fig.11 The resistance of the sensor prepared based on the dendrite composite gel in Example 1 changes according to different gestures when worn on the fingers. The five fingers have obvious signal differences under different gesture changes, which can effectively detect and identify changes in human limbs, proving the future application potential of sensors in the field of wearable devices.

[0067] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0068] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a conductive dendrite composite gel, characterized in that: The steps include: 1) dispersing a vinyl monomer, a photoinitiator and a crosslinking agent in water by ultrasonication to obtain a polymer prepolymer solution, and then initiating a polymerization reaction under ultraviolet light to form a hydrogel; The vinyl monomer is selected from: 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, dimethyl-(4-vinylphenyl) propane sulfonic acid ammonium or 3-(1-(4-vinylbenzyl)-1H-imidazol-3-ium) propane-1-sulfonate; The photoinitiator is selected from: 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, 2-hydroxy-2-methyl-1-phenylpropanone, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 1-hydroxycyclohexyl benzophenone or 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide; The cross-linking agent is selected from: N,N-dimethylacrylamide or N,N-methylenebisacrylamide; 2) soaking the hydrogel obtained in step 1) in a stannous chloride solution to obtain a hydrogel rich in stannous ions; 3) Externally connecting electrodes to both ends of the hydrogel rich in stannous ions obtained in step 2) and applying voltage to induce in-situ deposition of dendrites, followed by soaking and dialysis with deionized water to remove free Sn. 2+ ions to obtain a conductive dendrite composite gel.

2. The method for preparing the conductive dendrite composite gel according to claim 1, characterized in that: Step 1) In the polymer prepolymer solution, the content of the vinyl monomer is 1-8 mmol / mL, the content of the photoinitiator is 0.1-1 wt%, and the content of the crosslinking agent is 0.05-2 wt%.

3. The method for preparing the conductive dendrite composite gel according to claim 1, characterized in that: In step 1), the polymerization reaction temperature is room temperature and the time is 0.5 to 12 hours.

4. The method for preparing the conductive dendrite composite gel according to claim 1, characterized in that: In step 2), the concentration of the stannous chloride solution is 0.05 to 6 mol / L, and the soaking time is 2 to 48 hours.

5. The method for preparing the conductive dendrite composite gel according to claim 1, characterized in that: In step 3), the external electrode is a metal tin electrode, the applied voltage ranges from 1 to 10 V, and the power-on time is 1 to 10 minutes.

6. The method for preparing the conductive dendrite composite gel according to claim 1, characterized in that: In step 3), the dialysis time of deionized water soaking is 12 to 60 hours, and the deionized water is replaced several times during the soaking process.

7. The conductive dendrite composite gel prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the conductive dendrite composite gel as claimed in claim 7 as a wearable flexible strain sensor.

Citation Information

Patent Citations

  • Dual network hydrogel-derived graphene / tin-nickel alloy composite material as well as preparation method and application thereof

    CN107528052A

  • Preparation method and application of flexible and dendritic-crystal-resistant hydrogel electrolyte membrane

    CN116103921A

  • Gel electrolyte and preparation method and application thereof

    CN118185072A

  • Hydrogel, method for producing same, and use of same

    WO2018168782A1